Respostas
respondido por:
4
Bom dia Lucas
z = 1 + 2i
w = 2 - 3i
w' = 2 + 3i (conjugado)
z/w = (1 + 2i)/(2 - 3i)
z*w'/ww' = (1 + 2i)*(2 + 3i)/((2 - 3i)*(2 + 3i)) =
(2 + 3i + 4i - 6)/(4 + 9) = (-4 + 7i)/13
z = 1 + 2i
w = 2 - 3i
w' = 2 + 3i (conjugado)
z/w = (1 + 2i)/(2 - 3i)
z*w'/ww' = (1 + 2i)*(2 + 3i)/((2 - 3i)*(2 + 3i)) =
(2 + 3i + 4i - 6)/(4 + 9) = (-4 + 7i)/13
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás